Epidemiology and mortality rate of thyroid storm in Thailand: Analysis using a national in-patient database - Jin Sothornwit; Suranut Charoensri; Dueanchonnee Sribenjalak; Chatlert Pongchaiyakul (PLOS One, 2026)
Objective To investigate the nationwide incidence, temporal trends, of thyroid storm among hospitalized patients with thyrotoxicosis in Thailand, to compare in-hospital mortality between patients with and without thyroid storm, and to identify independent predictors of mortality and healthcare resource utilization among patients with thyroid storm. Methods A retrospective population-based study was conducted using the National Health Security Office database (2017–2024), including adult patients hospitalized with thyrotoxicosis recorded as the principal diagnosis. Thyroid storm was identified by ICD-10 code E05.5, while other thyrotoxicosis diagnoses without thyroid storm served as the comparator group. Temporal trends in incidence were assessed by Poisson regression, and multivariable logistic regression models identified independent predictors of mortality and prolonged length of hospital stay among patients with thyroid storm. Results Among 4,418 admissions with thyrotoxicosis as the principal diagnosis, 1,160 (26.2%) were thyroid storm and 3,258 (73.8%) were thyrotoxicosis without thyroid storm. The average annual incidence was 0.22 cases per 100,000 person-years, rising from 0.15 (2017) to 0.32 (2024) (p for trend < 0.001). In-hospital mortality was significantly higher in patients with thyroid storm than in those without (18.0% versus 1.0%; p < 0.001). After multivariable adjustment, thyroid storm was independently associated with increased mortality (aOR 11.17; 95% CI 7.41–16.85; p < 0.001). Septic shock (aOR 5.26), cardiogenic shock (aOR 4.90), and acute kidney injury (aOR 3.72) were the strongest independent predictors of death. The median length of hospital stay was 6 days (P25-P75 4–10). Conclusions The incidence of thyroid storm in Thailand is rising, with a high in-hospital mortality of 18.0%. Mortality is independently driven by advanced age, male sex, chronic liver disease, and acute multi-organ complications, particularly septic shock, cardiogenic shock, and acute kidney injury. Prolonged hospitalization is largely driven by pneumonia, acute kidney injury, and chronic liver disease. Early recognition and aggressive management of precipitating factors, particularly pneumonia, and expanded insurance coverage for advanced therapies are essential to improve survival.